Mesolimbic neuropeptide W coordinates stress responses under novel environments - Motoike, Toshiyuki (Proc Natl Acad Sci U S A, 2016)
Neuropeptide B (NPB) and neuropeptide W (NPW) are endogenous neuropeptide ligands for the G protein-coupled receptors NPBWR1 and NPBWR2. Here we report that the majority of NPW neurons in the mesolimbic region possess tyrosine hydroxylase immunoreactivity, indicating that a small subset of dopaminergic neurons coexpress NPW. These NPW-containing neurons densely and exclusively innervate two limbic system nuclei in adult mouse brain: the lateral bed nucleus of the stria terminalis and the lateral part of the central amygdala nucleus (CeAL). In the CeAL of wild-type mice, restraint stress resulted in an inhibition of cellular activity, but this stress-induced inhibition was attenuated in the CeAL neurons of NPW(−/−) mice. Moreover, the response of NPW(−/−) mice to either formalin-induced pain stimuli or a live rat (i.e., a potential predator) was abnormal only when they were placed in a novel environment: The mice failed to show the normal species-specific self-protective and aversive reactions. In contrast, the behavior of NPW(−/−) mice in a habituated environment was indistinguishable from that of wild-type mice. These results indicate that the NPW/NPBWR1 system could play a critical role in the gating of stressful stimuli during exposure to novel environments.